2020
DOI: 10.1038/s41523-020-00186-5
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of biologic factors for the staging of de novo stage IV breast cancer

Abstract: This study aimed to investigate the prognostic value of biological factors, including histological grade, estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor-2 (HER2) status in de novo stage IV breast cancer. Based on eligibility, patient data deposited between 2010 and 2014 were collected from the surveillance, epidemiology, and end results database. The receiver operating characteristics curve, Kaplan–Meier analysis, and Cox proportional hazard analysis were used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
2
8
1
Order By: Relevance
“…32 More recent studies have proposed dividing the M1 stage in de novo MBC. [29][30][31] Our findings support modifying the current M1 stage 75,76 by classifying patients with de novo MBC into prognostic categories using a combination of clinical and tumor characteristics.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…32 More recent studies have proposed dividing the M1 stage in de novo MBC. [29][30][31] Our findings support modifying the current M1 stage 75,76 by classifying patients with de novo MBC into prognostic categories using a combination of clinical and tumor characteristics.…”
Section: Discussionsupporting
confidence: 63%
“…Given the heterogeneity of MBC outcomes, the results presented here could also support a novel substaging classification for patients with MBC. [29][30][31][32]…”
mentioning
confidence: 99%
“…According to world literature, patients with HER2+ tumors have better outcomes in the metastatic setting than those with HER2-negative or triple-negative tumors. 12 , 21 , 27 , 29 However, in this study, although the highest mortality rate was observed in patients with triple-negative tumors, those with HER2+ BC had the highest progression rate. This is probably because Colombia’s health system structure promotes a differentiated and unequal health care for its citizens, based mainly on their financial capacity.…”
Section: Discussioncontrasting
confidence: 49%
“…Neuman et al 26 noted that the status of hormone and HER2 receptors were the variables that best predicted survival in de novo MBC; but, unlike the present work, they observed that patients with HER2+ tumors had better survival, something they attributed to the availability of effective targeted therapy. He et al 27 also studied the value of some biological factors in de novo MBC, finding that patients with high-grade, HER2-negative, single hormone receptor-positive, or triple-negative tumors had lower BC-specific survival. These biomarkers showed a good prognostic performance so the authors consider it worthwhile to incorporate them into a new staging system for patients diagnosed in stage IV, as occurs in the 8th edition of the American Joint Committee on Cancer staging system for non-metastatic BC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation